Cleavable and removable polymer thermosets for organic field effect transistor packaging - Arulkashmir, Arulraj; Bhosale, Manik E.; Krishnamoorthy, Kothandam (RSC Advances, 2013)
Recent years have witnessed tremendous progress in the design and synthesis of electroactive materials for the fabrication of organic electronic devices. However, very little research effort has been devoted to developing organic packaging materials, which are crucial for the efficient functioning of the devices. Polymer thermosets (PTs) are extensively used for the packaging of microelectronic and optoelectronic devices. Although PTs are effective in providing mechanical stability and environmental protection to devices, the removal of PTs without destroying the underlying surface is cumbersome. Facile removal of PTs is essential to reuse the expensive substrates. Herein, we report the preparation of a thermoset using an aliphatic disulfide containing cross-linker, cystamine. By varying the cross-linker concentration, the mechanical property of the thermoset was varied from ductile to brittle. The ductile thermoset was coated on metal, semiconductor and flexible substrates. The thermosets were then cleaved using a biomolecule in neutral pH. We have demonstrated that the cleavage and removal of thermosets don't affect the surface properties of the underlying substrates. Furthermore, the thermosets were coated on top of organic field effect transistors to provide environmental protection. The thermoset coated devices showed a charge carrier mobility of 5.3 x 10(-3) cm(2) V-1 s(-1). Then, the thermoset was cleaved and removed, and the substrate was reused for the fabrication of organic field effect transistors with unchanged device efficiencies.